The Impact of Disasters on Urban Structure: A Study of North Lombok, West Nusa Tenggara, Indonesia - Wiyono, Agus; Alidrusb, Sammy; Faustc, Heiko (Journal of Ecohumanism, 2024)
Indonesia, with its archipelagic geography and location on the Pacific Ring of Fire, is highly susceptible to a range of natural disasters, including earthquakes, volcanic eruptions, tsunamis, and landslides. Rapid urbanization and population growth have exacerbated this vulnerability, placing millions of people in high-risk areas. This study focuses on North Lombok Regency, an area severely affected by the 2018 earthquake, to analyze the subsequent changes in urban structure, land use, and the effectiveness of spatial planning and recovery strategies. The research employs a qualitative approach, combining field surveys, interviews, and secondary data analysis to examine the spatial and functional changes in the urban environment post-disaster. The findings reveal significant alterations in land use, with a reduction in built-up areas and an increase in open spaces and vegetative cover, driven by the need to avoid rebuilding in high-risk zones. The study also highlights the critical role of spatial planning adjustments, such as the implementation of new zoning regulations and the relocation of critical infrastructure, in enhancing urban resilience. Community resilience emerged as a key factor in the recovery process, with participatory planning and local engagement leading to quicker and more sustainable outcomes. The study underscores the importance of integrating hazard risk assessments into urban planning and the need for resilient infrastructure development to maintain urban connectivity and support long-term economic recovery. This research contributes original insights by applying a multi-theoretical framework, including Urban Resilience Theory, Social Capital Theory, and Geographical Determinism, to analyze disaster impacts and recovery dynamics. The implications extend beyond North Lombok, offering valuable lessons for disaster-prone regions globally on how to build more resilient communities through strategic land use, community participation, and adaptive management practices.